Evaluation of the effectiveness of Aquatain, Bacillus thuringiensis var. israelensis, and Temephos on Anopheles arabiensis and Anopheles stephensi larvae in the laboratory and field settings - Sisay Dugassa; Tilahun Kebede; Bedri Abdulatif; Gudissa Assefa; Hiwot Solomon; Dejene Getachew; Kidane Lelisa; Araya Gebresilassie (Parasites & Vectors)
Abstract Background The main tools to control malaria vectors in sub-Saharan Africa are long-lasting insecticidal nets and indoor residual spraying. However, their sustainability is threatened by the emergence of insecticide resistances, behavioral avoidance and presence of outdoor biting mosquito populations. Thus, complementary interventions such as larval source management, which includes larviciding, are required to achieve better results in malaria vector control. This study aimed to evaluate the effectiveness of three larvicides (Aquatain AMF®, Temephos and Bacillus thuringiensis var. israelensis) against larvae of Anopheles arabiensisi and Anopheles stephensi. Methods The tests on insectary colony and field-collected immature stages of the mosquitoes were conducted in the laboratory. For this, the third and fourth larval instars of An. arabiensis and An. stephensi were placed in trays measuring 50 cm × 40 cm, and larvicides were applied to the treatments while the control trays were left untreated. In addition, the larvicides were applied to selected natural habitats, and their effects on the reduction of the immature stages’ density were estimated. Results In the laboratory, susceptible An. arabiensis showed mortality rates of 95% with Aquatain, 100% with Bti and 100% with Temephos, while An. stephensi showed 60% with Aquatain, 84% with Bti and 100% with Temephos. The percentage of larval mortalities among wild An. arabiensis collected from the field and exposed to Aquatain, Bti and Temephos were 97%, 100% and 100%, respectively, whereas those of An. stephensi were 74%, 99% and 100%, respectively. During the natural field study, the reductions in immature stages were as follows: 77%, 96% and 95% in Adama; 89%, 95% and 94% in Metahara; and 92%, 84% and 96% in Awash for Aquatain, Bti and Temephos, respectively. Conclusions The three larvicides, Aquatain, Temephos and Bti, provided high levels of larviciding efficacies in both laboratory and field evaluations. Despite its effectiveness, Temephos caused the water to turn whitish and emitted a strong odor that made the community wary regarding the treated habitats. Therefore, we recommend using Aquatain in mosquito control programs as a complementary malaria vector control tool. Graphical Abstract